2021
DOI: 10.18203/2349-3291.ijcp20213736
|View full text |Cite
|
Sign up to set email alerts
|

A study of correlation of foot length and new Ballard score in determining the gestational age of newborns

Abstract: Background: Gestational age (GA) estimation plays a vital role in obstetric, perinatal and neonatal care. Foot length (FL) measurement can serve as a simple, easy and cost effective parameter for estimating GA. The aim of this study was to determine correlation between foot length of new born and GA by new Ballard score and forming a percentile chart if a positive correlation was found.Methods: GA assessment of newborns born in our hospital was done by new Ballard score within 24 hours of life. FL was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…This is supported by more recent studies which have demonstrated strong correlations between estimated gestational age and postnatal foot length. 11,12 Foetal growth is usually assessed by comparison of the weight, body length and OFC at birth with standards that define reference ranges at a spectrum of gestational ages, called the intrauterine growth charts. Lubchencho et al 13 developed the first intra-uterine growth charts involving only Caucasian neonates, and many more growth charts were developed in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by more recent studies which have demonstrated strong correlations between estimated gestational age and postnatal foot length. 11,12 Foetal growth is usually assessed by comparison of the weight, body length and OFC at birth with standards that define reference ranges at a spectrum of gestational ages, called the intrauterine growth charts. Lubchencho et al 13 developed the first intra-uterine growth charts involving only Caucasian neonates, and many more growth charts were developed in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by more recent studies which have demonstrated strong correlations between estimated gestational age and postnatal foot length. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%